MORAL EDUCATION OF STUDENTS THROUGH THE ART OF MUSIC AND SINGING - Askarova Sohibakhon Mukhammadzhonovna,; Kusherbayev Zhanbolat Asetovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In today's rapidly changing world, when such global problems arise as the attack of various ideas and information, the issues of moral education of the younger generation through the transfer of knowledge using various means and methods, the organization of music classes in the moral education of children, constitute the main content of this article. Also, the influence of musical art and songs on the worldview and morals of children in society is considered through the works of great scientists, shown by experimental works, and a conclusion is presented.